South-south migration: the impact of Nicaraguan immigrants on earnings, inequality and poverty in Costa Rica - T. H. Gindling (Institute for the Study of Labor (IZA), 2008)
More than half of those who emigrate from developing countries move to other developing countries, yet there have been few studies of the impact of this South-South migration. In this paper, we examine the impact of migration from one developing country, Nicaragua, on the labor market in another developing country, Costa Rica. We find little evidence to support the hypothesis that Nicaraguan migration to Costa Rica was an important factor contributing to falling earnings, increased inequality or stagnating poverty in Costa Rica.
Keywords: J61; 300; Costa Rica; Latin America; migration; earnings; inequality; poverty; Internationale Wanderung; Süd-Süd-Beziehungen; Einwanderung; Arbeitsmarkt; Lohnstruktur; Einkommensverteilung; Armut; Costa Rica; Auswanderung; Nicaragua